A Nature's Way-Our Way Pilot Project Case Assemblage: (Re)Storying Child/Physical Literacy/Land Relationships for Indigenous Preschool-Aged Children's Wholistic Wellness - Kathryn Riley; Amanda Froehlich Chow; Kathleen Wahpepah; Natalie Houser; Mariana Brussoni; Erica Stevenson; Marta C. Erlandson; M. Louise Humbert (MDPI AG, 2023)
Physical literacy (PL) is gaining more attention from educational policy-makers, practitioners, and researchers as a way to improve health and wellness outcomes for children and youth. While the development of PL is important for early years children, there is limited attention in the literature that explores the political, cultural, and social discourses imbued in colonialism that implicate how PL is actualized in Indigenous early childhood education (ECE) contexts. This case assemblage explores how the culturally rooted, interdisciplinary, and community-based PL initiative, Nature's Way-Our Way (NWOW), negotiated movement with three early childhood educators in the pilot project with an early childhood education centre (ECEC) in Saskatchewan, Canada. Through postqualitative approaches to research, this case assemblage adopts new materialist methodologies to show how the natural order of knowing in movement was disrupted through moments of rupture generating stories of PL to encompass radical relationality with land. As land becomes a vital and lively part of PL storying, it can function as an important protective factor for Indigenous preschool-aged children's wholistic wellness.